Development of a soil test for determining the impact of soil disturbance - Torbert, H. A.; Gebhart, D. L. (Agrociencia Uruguay, 2012)
United States Federal law requires land-managing agencies like the US Army to identify and take into account the impacts of their undertakings on archaeological resources. Development of a method that uses changes in the stratification of horizon interfaces to identify the onset of adverse impacts to archaeological deposits was investigated. This method will allow Cultural resource managers to identify types and levels of military training that risk adverse impacts to intact archaeological deposits. A study was initiated at Fort Benning, GA, and Fort Riley, KS with treatments including (1) archaeological habitation/no-training, (2) archaeological habitation/training, (3) non-habitation/no-training, and (4) non-habitation/training. Soil core samples for each treatment group were taken for 0-10, 10-20, 20-30, 30-50 cm increments for chemical analysis. Several promising elements were identified that may be useful as indicators for determining potential damage to archaeological deposits resulting from ground disturbing activities such as mechanized maneuver training. Differences between disturbed and undisturbed treatment groups were often evident at depths of 20-40 cm, indicating substantial soil inversion, displacement, or mixing. Soil C concentrations were always negatively impacted in disturbed treatment group soils, indicating that C might also be a reliable indicator of disturbance, especially when used in a ratio with another elements that accumulate in undisturbed surface soil horizons. Analyses of ratios, including the Top-to-Total (ratio of upper 10 cm to entire 50 cm profile), the Total-to-Soluble (ratio of total elemental to soluble elemental concentration), and the Leachable to Non-Leachable (ratio of leachable/mobile element to a nonleachable/ immobile element) indicated promising results.